Levantamento e análise de possíveis influentes nos autos de infração voltados a poluição atmosférica lavrados pela CETESB em uma mineradora no município de Cajati/SP - Souza, Júlia Fraidemberge de (Universidade Federal de São Carlos, 2024)
Being considered a heritage of humanity, the environment has been increasingly included in global and national legislation in order to avoid environmental degradation. Due to the excessive exploitation of assets, it became necessary to impose penalties on those who did not comply with the legislation, which aims to protect environmental assets. Data made available on environmental crimes committed in a region are essential for understanding the dynamics of human action on the environment, being able to direct public policies and, furthermore, providing tools for planning and defining better strategies for decision-making, such as preventing, combating and monitoring environmental crimes and infractions. The present work aimed to analyze the environmental occurrences recorded in a mining company in the municipality of Cajati/SP in order to verify which environmental factors could be related to the infractions. The methodology starts from a study with secondary data in the CETESB database (environmental licensing body of the state of São Paulo), through the analysis of environmental occurrences recorded in the municipality in mining companies and articles and scientific theses published in trusted channels. The data were organized in spreadsheets using the Microsoft Excel application and analyzed using descriptive statistics. The results obtained provide a better understanding of the environmental issues in the region and also highlight the relevant role played by CETESB.
Survey and analysis of possible influences in infringement reports concerning atmospheric pollution carried out by CETESB in a mining company in the municipality of Cajati/SP
Keywords: Mineração; Autuação; Licenciamento; Poeiras fugitivas; Mosaic; Mining; Penalty; Licensing; Fugitive dust; ENGENHARIAS::ENGENHARIA MECANICA::ENGENHARIA TERMICA::CONTROLE AMBIENTAL